Atitudes relativas a meios de comunicação: um estudo exploratório sobre o Wap - Schoeninger, Carlos Raimar (2002)
The new economy stimulated by the bigger Internet participation as an interaction mean between people and business has been changing the companies¿ management routine. Nowadays, Internet access goes through telephones, in the houses and offices, or through nets of the Intranet kind, with the users in their working settings. The Internet personal access added, with mobility, surely will bring changes to our contacting form to the outside world as well as it will create a possibility of giving the customers a bigger variety of products and services. The present study aims are: (i) to verify the customers behaviours related to this new media, presented in the mobiles digital screens; (ii) to explore some of their main features, and (iii) to compare them with the other media features, as the radio and the TV ones. The applied research methodology was the data collecting through phone interviews. To obtain a Confidence Interval of 95%, 470 WAP, Internet, radio and TV current users¿ answers were gotten. To compare the media, the Fishbein multi-attributes model was used what possibilities to form comparative scores of the attributes built for the research. To mark the discussion concerning the public behaviour related to the differentiated use of the mentioned media out, the study produced uses the McLuhan theoretical reference (1969), specially concerning to his theoretical building, denominated hot and cold means. But this referential theoretic mark could not be supported by the accomplished quantitative study result. The comparison of built attribute scores averages has differentiated the hot media WAP, like radio, as well as the cold media one, like TV. This way, showing that the access new technology appearance, WAP, not only enlarges the Internet use, but also appoints to a new theoretic classification possibility to this new media. The accomplished quantitative research revealed that, through the user point of view, the ¿Contents¿ category is considered as one of the most important WAP aspects. The TV and the radio received significantly lower grades in this subject. The public considers that is important that the WAP information is ¿trustworthy¿, ¿easy¿ to find, ¿available¿, ¿sufficient¿ and that attends the ¿urgency¿ expected by the user. It was observed that the WAP score ¿emotion¿ is inferior to the radio and TV and superior to the Internet ones. But, the differences found are not significant. Considering the low score of importance given to the attributes group ¿emotion¿, is not recommended the WAP use as media when the emotional users aspects are wanted to be reached.